Tumor-specific T cell-mediated upregulation of PD-L1 in myelodysplastic syndrome cells does not affect T-cell killing - Ferrari, Valentina; Tarke, Alison; Fields, Hannah; Tanaka, Tiffany N.; Searles, Stephen; Zanetti, Maurizio (Frontiers in Oncology, 2022)
The PD-1:PD-L1 axis is a binary interaction that delivers inhibitory signals to T cells, impeding both immune surveillance and response to immunotherapy. Here we analyzed a phenomenon whereby tumor-specific T cells induce PD-L1 upregulation in autologous MDS cells in short-term culture, through a mechanism that is cell-contact-independent and partially IFN-dependent. After investigating a panel of small molecule inhibitors, we determined that PD-L1 upregulation was attributed to the PKR-like ER kinase (PERK) branch of the unfolded protein response. Interestingly, we found that the cytotoxic capacity of tumor-specific T cells was not impaired by the expression of PD-L1 on MDS target cells. These results highlight a little appreciated aspect of PD-1:PD-L1 regulation in hematologic cancers and indicate that this phenomenon, while likely to hinder autochthonous immune surveillance, may not be an obstacle to immunotherapies such as personalized adoptive T cell therapy.